OTU-030 Faecal microbiota transplantation for recurrent clostridium difficile infection: real world uk data. (8th June 2018) - Digby-Bell, Jonathan; Patel, Kamal; Mutalib, Mohamed; Irving, Peter; Goldenberg, Simon
Abstract : Introduction: recurrent Clostridium difficile infection (rCDI) is a medically challenging condition with limited therapeutic options often resulting in repeated admissions to hospital with associated high financial and patient burden. Faecal microbiota transplantation (FMT) has been shown to be highly effective treatment in placebo-controlled trials, however little real life data exists particularly from UK centres. We report our experience in a single tertiary referral centre. Method: Data was collected prospectively from January 2015 to November 2017 for patient demographics, comorbidities, route of FMT administration, 30 day and 1 year mortality. Primary endpoint was resolution of diarrhoea without relapse 10 weeks after first FMT. Resolution of diarrhoea without relapse 10 weeks after second FMT was also recorded. Results: 35 adult and 2 paediatric patients were approved for FMT for treatment of rCDI of which 35 patients underwent the procedure. 2 patients clinically deteriorated before FMT could be performed such that FMT became inappropriate. 27/35 (77%) were female, with a mean age of 67 y (range 4–91), and a mean ASA grade of 2.0 (0–4). Patients had received 3.1 (2–5) courses of antibiotics for clostridium difficile and 27 (77%) were external referrals. 32 FMTs were performed via colonoscopy and 3 via nasojejunal tube. 3 patients died within 30 days of FMT (mean ASA grade 3.3) but none directly related to the FMT or C Diff. There was once further expected death 90 days after FMT. No other major side effects or safety concerns were seen. Of the patients who survived to day 30; 28 out of 32 (87.5%) patients had cessation of diarrhoea without relapse after 10 weeks. 4 patients had recurrent diarrhoea within 10 weeks of FMT of whom 2 had a 2nd FMT resulting in cessation of diarrhoea with no relapse after 10 weeks. The other two patients clinically deteriorated due to underlying medical conditions such that a 2nd FMT was inappropriate. All patients who survived had resolution of symptoms after their first or second transplant. Conclusion: FMT is a highly effective treatment for rCDI in the real world with resolution of symptoms and no relapse after 10 weeks achieved in 89.7% of patients undergoing 1 st FMT increasing to 100% after a 2nd FMT. No safety concerns were identified during the study period. The 3 deaths within 30 days of FMT highlight the comorbid population who develop rCDI and better patient selection is required to ensure appropriateness of FMT in high risk groups.